Proceedings of the 27th Annual ACM Symposium on Applied Computing 2012
DOI: 10.1145/2245276.2232116
|View full text |Cite
|
Sign up to set email alerts
|

A provenance approach to assess the quality of geospatial data

Abstract: Geographic information is present in our daily lives. This pervasiveness is also at the origin of several problems, including heterogeneity and trustworthiness -of the data sources, of the data providers, and of the data products derived from the original sources. Most efforts to improve this situation concentrate on establishing data collection and curation standards, and quality metadata. This paper extends these efforts by presenting an approach to assess quality of geospatial data based on provenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ouma et al [40] downsized the quality measures from global to national perspective and proposed an alternative set of quality dimensions encompassing both quantifiable and subjective ones. Malaverri and Medeiros [41] developed a meta-study surveying the use of quality measures/dimensions in agricultural applications as well as the context of use. Their observations revealed that the most often mentioned (and probably used) dimensions are accuracy, timeliness, and completeness, followed by consistency and relevancy.…”
Section: Data Quality and Uncertaintymentioning
confidence: 99%
“…Ouma et al [40] downsized the quality measures from global to national perspective and proposed an alternative set of quality dimensions encompassing both quantifiable and subjective ones. Malaverri and Medeiros [41] developed a meta-study surveying the use of quality measures/dimensions in agricultural applications as well as the context of use. Their observations revealed that the most often mentioned (and probably used) dimensions are accuracy, timeliness, and completeness, followed by consistency and relevancy.…”
Section: Data Quality and Uncertaintymentioning
confidence: 99%
“…There are a number of studies, that have used provenance in the geospatial domain [10], [11], [12], [13]. For example, Wang et al [10] propose a provenance-aware architecture to record the lineage of spatial data in Geographic Information Systems (GIS).…”
Section: Related Workmentioning
confidence: 99%
“…Previous applications of trust models for spatial datasets (Malaverri et al, 2012) and crowdsourced geographic features (Bishr & Mantelas , 2008;Celino, 2013) have produced a scalar value as a proxy for trustworthiness. This can then be employed in much the same way as metadata or provenance information to give an indication of data quality.…”
Section: Direction Of Researchmentioning
confidence: 99%